A prediction of the dispersal of Eucryptorrhynchus scrobiculatus (Coleoptera: Curculionidae) adults in the field and laboratory. Issue 3 (3rd March 2020) - Xiao-Yi, Wang; Gan-Yu, Zhang; Jun-Bao, Wen
ABSTRACT: Eucryptorrhynchus scrobiculatus (Motschulsky) is a host-specific root-feeding pest of the tree-of-heaven tree, Ailanthus altissima (Mill.) Swingle, in China. The trunk trap net (TTN) with a wire ring and a TTN with a moist sponge cushion have captured a large number of these weevils. The dispersal ability of weevils may undermine eradication efforts for this pest. Tree-of-heaven is an invasive plant in the United States. Studies have shown that the closely related species E. scrobiculatus and E. brandti, are potential biological control agents for A. altissima in the United States. In this study, we evaluated the dispersal ability of E. scrobiculatus in the field and laboratory to further investigate its use as a biological control agent. We released 1, 800 E. scrobiculatus in each of two plots using a mark-release-recapture method and captured 12.5% ( n  = 225) of the weevils in the plot with an attractant and 10.9% ( n  = 197) of the weevils in the plot without an attractant. The results show that the dispersal distance equation of E. scrobiculatus throughout the time is y  = 44.5844 + 0.8252 x –0.0074x² + C + D. The maximum dispersal distance in the field was 67.5  m after 60 days and the mean dispersal distance was 1.14  m day −1 . We determined that wounded A. altissima increased the dispersal of E. scrobiculatus, especially for males. The dispersal rate of E. scrobiculatus increased with wind speeds of 1.8– 3.1  m s −1 .